THE USE OF PEER ASSISTED LEARNING FOR PRE_SERVICE STUDENTS IN CREATING LESSON PLAN - Martriwati; Burhayani (ELLTER Journal, 2023)
Peer Assisted Learning is an active discussion and cooperative learning method within the framework of a partnership in the peer-aged group with the formal structures of the course. PAL is learning that is carried out by fellow students and does not involve professional lecturers in the process. This study aims to explore in depth students' perceptions of PAL in the learning process at the Education Study Program at UHAMKA. This research is a qualitative research with a phenomenological approach and the technique of taking participants in this study with maximal variation sampling. The main participants in this study were students from the 2021 totaling 24 people consisting of men and women who were peer tutors and peer tutors. Retrieval of main data through focus group discussions 3 times, while as data triangulation the researcher used in-depth interview techniques with the subject lecturers who held the PAL and observed PAL activities. There are various student perceptions regarding the definition and benefits of PAL, as well as factors that influence PAL, which includes supporting factors such as good communication from peer tutors and the material provided by peer tutors is in accordance with the learning objectives. Factors that hinder the process of implementing PAL include readiness for implementation, readiness for peer tutors, and readiness for peer tutors. In addition, there are also student perceptions regarding expectations for the implementation of PAL, namely the application of PAL in TEFL 3 (Teaching Practice lesson), the use of technology, and evaluation in its implementation. Student perceptions of PAL, namely peer tutors and peer tutors influence each other in their implementation.